Analisis Nilai Amplitudo Jembatan Rangka Baja Menggunakan Beban Berjalan Dengan Metode Fast Fourier Transform (FFT) - Bagus Acung Billahi; Kukuh Wisnuaji Widiatmoko; Faizal Mahmud (Jurnal Teknik Sipil, 2025)
A steel truss bridge is a structure constructed from a series of interconnected steel bars. The loads received by this structure are analyzed and transferred to the steel bars that make up the structure. Factors that need to be analyzed in bridge construction include the location and surrounding environmental conditions. After identifying the type of soil and bedrock beneath the surface, the materials used must meet strength or durability test standards before the bridge can be operated. The materials used must comply with the Indonesian National Standard (SNI). In addition to the factors mentioned above, the bridge must undergo a feasibility evaluation. Among the various tests used to evaluate bridge strength, one is vibration testing. The vibration test method, when compared to the load test method, shows higher cost efficiency and does not cause damage to the structure.